DIVERSITY AND CARBON STOCKS OF GENUS FICUS IN GUNUNG TILU KUNINGAN DISTRICT, WEST JAVA PROVINCE, INDONESIA - Yayan Hendrayana; Ilham Adhya; Agus Yadi Ismail (Journal of Forestry And Environment, 2018)
Moraceae is one of the dominant families in the forest area of  Gunung Tilu, Kuningan Regency which is one of the lowland forests. Lowland tropical forest has the highest damage risk compared to other forest types. This study aims to determine the diversity and carbon reserves of the Ficus genus in the forest of Gunung Tilu, Kuningan District, West Java. This study was conducted in July - September 2017 by making a sample plot with an area of 9.6 ha. Measurement of tree biomass was carried out by method without logging. All trees with DBH 20 cm in diameter measured and recorded the type name. A total of 1,058 individuals consisting of 42 families and 149 species with DBH 20 cm, it has been found in the sample plot of Gunung Tilu forest namely Ficus sundaica Blume, Ficus virens Aiton var. glabella, Ficus drupacea Thund, Ficus kurzii King, and Ficus benjamina L are the dominant Ficus species based on the Important Value Index (IVI). While the diversity of Ficus spp is moderate. The amount of tree biomass and carbon stock in the study site are 606,75 ton ha-1 and 303,38 ton C ha-1.Keywords: Ficus Genus, diversity, carbon reserve,  Gunung Tilu